Grade complaint procedure: a chance to improve teaching - Polo Martínez, Ignacio; Puertas Bescós, Gemma (Avances en Supervisión Educativa, 2019)
During teachers’ training, 48% of them in Spain (according to TALIS, 2018), have studied the contents of their subjects, specific and general teaching and practice in the classroom. However, this average is lower than the average in OECD countries and economies that participate in TALIS (79%). Although this trend seems to decrease in the last five years, most teachers admit to have training needs in "student assessment practices" and "teaching students with special needs." Considering teachers’ functions set by the Organic Law of Education in its article 91.1, the fact that teachers in Spain have difficulties with the evaluation of their students and the support to their educational process, this could affect directly to the improvement plan of our educational system. Sometimes, families show their disagreement with the grades assigned to a student, and/or about the promotion/degree decision and/or about the support raised to their children (especially in ESO and Baccalaureate, but also, in the last years, in Primary school). This disagreement can turn into a formal grade complaint. Some regions in Spain have set this complaint procedure, however no advisory processes have been found from the Administration (Inspection) to the schools. With this article, we pretend to help teachers to know what should be analiced in a complaint in the school, and by the Inspection itself if it arrives there. Related to the same advisory function from intendants, this document can be used by families to know the rights that the different standards operatives define. Anyway, this document should be consider as a chance to improve as a professional and not as a threat.
Keywords: evaluation; qualification; differences; grade complaint; families; teacher; supervision